AMazING - Advanced Mobile wireless playGrouND - Barraca, João (2012)
We describe a wireless testbed composed of 24 wireless nodes that can be used to perform a broad range of studies in the area of next generation networks. This paper addresses the difficulties and constrains faced by the authors throughout the deployment process of such testbed. Flexibility and controllability were key concerns driving the testbed design. The testbed can be remotely managed through a series of remotely accessible web services performing low level management. Validation results are presented, showing the interference levels of the testbed as well as its maximum throughput capabilities.